Assessment of Hypoglycemic Trace Elements in Bitter Gourd (Momordica charantia) Fruit by Neutron Activation Analysis - As’ari, Ahmad Hasan; Istanto, Istanto; Suprapti, Siti; Yusuf, Saeful (Jurnal Ilmiah Aplikasi Isotop dan Radiasi, 2021)
The fruit of bitter gourd (Momordica charantia) or commonly known in Indonesia by pare is believed to reduce glucose levels in the blood. It is known that several trace elements affect insulin performance, such as chromium, magnesium, zinc, and manganese. This study aims to determine the content of hypoglycemic trace elements in bitter gourd fruits using neutron activation analysis techniques. The gourd fruits were taken from four regions in Java, i.e. Bangkalan, Magelang, Cianjur, and Pandeglang. The results showed that bitter gourd fruit contained elements with average contents in mg/kg dry weight: chromium (1.647), magnesium (2881), zinc (30.1), and manganese (57). The gourd fruit from Pandeglang has three elements with the highest concentration, namely chromium, magnesium, and manganese, whereas the highest zinc concentration comes from Cianjur. Based on the recommended dietary allowance of these elements and the level of consumption, bitter gourd fruit contributed chromium, magnesium, zinc, and manganese by 31%, 6%, 2%, and 7-18% daily intake. Furthermore, in vivo studies need to be carried out based on elemental content to determine the effectiveness of bitter ground fruit against diabetes.